Inhibitory interplay between orexin neurons and eating - González, JA; Jensen, LT; Iordanidou, P; Strom, M; Fugger, L; Burdakov, D (Elsevier, 2016)
In humans and rodents, loss of brain orexin/hypocretin (OH) neurons causes pathological sleepiness [1, 2, 3, 4], whereas OH hyperactivity is associated with stress and anxiety [5, 6, 7, 8, 9, 10]. OH cell control is thus of considerable interest. OH cells are activated by fasting [11, 12] and proposed to stimulate eating [13]. However, OH cells are also activated by diverse feeding-unrelated stressors [14, 15, 16, 17] and stimulate locomotion and “fight-or-flight” responses [18, 19, 20]. Such OH-mediated behaviors presumably preclude concurrent eating, and loss of OH cells produces obesity, suggesting that OH cells facilitate net energy expenditure rather than energy intake [2, 21, 22, 23]. The relationship between OH cells and eating, therefore, remains unclear. Here we investigated this issue at the level of natural physiological activity of OH cells. First, we monitored eating-associated dynamics of OH cells using fiber photometry in free-feeding mice. OH cell activity decreased within milliseconds after eating onset, and remained in a down state during eating. This OH inactivation occurred with foods of diverse tastes and textures, as well as with calorie-free “food,” in both fed and fasted mice, suggesting that it is driven by the act of eating itself. Second, we probed the implications of natural OH cell signals for eating and weight in a new conditional OH cell-knockout model. Complete OH cell inactivation in adult brain induced a hitherto unrecognized overeating phenotype and caused overweight that was preventable by mild dieting. These results support an inhibitory interplay between OH signals and eating, and demonstrate that OH cell activity is rapidly controllable, across nutritional states, by voluntary action.